Logic Programming and Nonmonotonic Reasoning 13th International Conference, LPNMR 2015, Lexington, KY, USA, September 27-30, 2015. Proceedings - Calimeri, Francesco; Ianni, Giovambattista; Truszczynski, Miroslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume contains the refereed proceedings of the 13th International Conference on Logic Programming and Nonmonotonic Reasoning, LPNMR 2015, held in September 2015 in Lexington, KY, USA. The 29 long and 11 short papers presented together with 3 invited talks, the paper reporting on the Answer Set Programming competition, and four papers presented by LPNMR student attendees at the doctoral consortium were carefully reviewed and selected from 60 submissions. LPNMR is a forum for exchanging ideas on declarative logic programming, nonmonotonic reasoning, and knowledge representation. The aim of the LPNMR conferences is to facilitate interactions between researchers interested in the design and implementation of logic-based programming languages and database systems, and researchers who work in the areas of knowledge representation and nonmonotonic reasoning.
Invited Talk: Stable Models for Temporal Theories -- Invited Talk: Algorithmic Decision Theory meets Logic -- Invited Talk: Relational and Semantic Data Mining -- Shift-design with Answer Set Programming -- Advances in WASP -- Improving Coordinated SMT-based System Synthesis by Utilizing Domain-specific Heuristics -- Integrating ASP into ROS for Reasoning in Robots -- Automated inference of rules with exception from past legal cases using ASP -- Online Action Language oBC+.-aspartame: Solving Constraint Satisfaction Problems with Answer Set Programming -- _Add Another Blue Stack of the Same Height!_: Plan Failure Analysis and Interactive Planning Through Natural Language Communication -- A Theory of Intentions for Intelligent Agents (Extended Abstract) -- Answer Set Programming modulo Acyclicity -- A Framework for Goal-Directed Query Evaluation with Negation -- Implementing preferences with aspirin -- Diagnosing Automatic Whitelisting for Dynamic Remarketing Ads Using Hybrid ASP -- Performance Tuning in Answer Set Programming -- Enablers and Inhibitors in Causal Justifications of Logic Programs -- Efficient Problem Solving on Tree Decompositions using Binary Decision Diagrams -- Knowledge Acquisition via Non-Monotonic Reasoning in Distributed Heterogeneous Environments -- Digital Forensics Evidence Analysis: An Answer Set Programming -- Approach for Generating Investigation Hypotheses -- A Formal Theory of Justifications -- A New Computational Logic Approach to Reason with Conditionals -- Interactive debugging of non-ground ASP programs -- Linking Open-world Knowledge Bases using Nonmonotonic Rules -- ASP, Amalgamation, and the Conceptual Blending Workflow -- Diagnostic Reasoning for Robotics using Action Languages -- OOASP: Connecting Object-oriented and Logic Programming -- Reasoning with Forest Logic Programs Using Fully Enriched Automata -- ASP Solving for Expanding Universes -- Progress in clasp series 3 -- Combining Heuristics for Configuration Problems Using Answer Set Programming -- Infinitary Equilibrium Logic and Strong Equivalence -- On the Relationship between Two Modular Action Languages: A Translation from MAD into ALM -- Compacting Boolean Formulae for Inference in Probabilistic Logic Programming -- Multi-Level Algorithm Selection for ASP -- Clause-Learning For Modular Systems -- Solving disjunctive fuzzy answer set programs -- Characterizing and Explaining Inconsistency in Logic Programs -- An Implementation of Consistency-Based Multi-Agent Belief Change using ASP -- ASPMT(QS): Non-monotonic spatial reasoning with Answer Set Programming Modulo Theories -- Mobile Robot Planning using Action Language BC with an Abstraction Hierarchy -- Logic Programming with Graded Modality.-The Design of the Sixth Answer Set Programming Competition -- Doctoral Consortium Extended Abstract: Planning With Concurrent Transaction Logic -- Doctoral Consortium Extended Abstract: Multi-context Systems with Preferences -- Doctoral Consortium Extended Abstract: Default Mappings in Ontology-Based Data Access -- Doctoral Consortium Extended Abstract: Nonmonotonic Qualitative Spatial Reasoning.
Keywords: Computer science; Computer programming; Software engineering; Computer logic; Mathematical logic; Computer science -- Mathematics; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Discrete Mathematics in Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Software Engineering; Programming Techniques; Electronic books